Nas águas do Prata: operações da Marinha brasileira entre 1854 e 1865 - Nas águas do Prata: operações da Marinha brasileira entre 1854 e 1865 (Navigator)
In the history of the Brazilian Navy the actions throughout the course the conflict against Paraguay are the most remembered in the second half of the nineteenth century. After Tonelero and before Riachuelo the naval force acted several times in the Rio de la Plata. Our goal is to present an overview of those little known actions, with emphasis on military aspects as well as to identify possible consequences for the War of the Triple Alliance.